Wartości w procesie wychowania rodzinnego - Skrzypniak, Ryszard (Wydawnictwo Naukowe UAM, 2000)
The theoretical-empirical article presents: • Firstly - theoretical, interdisciplinary considerations of system of values, it is concentrated the meaning of educational values in the process of upbringing. • Secondly - it analyses the results of researches on values of family in the course of transmission among generations, showing their relativism or constancy.
Values in the process of education in the family